Purposefulness of early application of physical rehabilitation means for improvement of external respiration system functional state of women with post mastectomies syndrome - Y.A. Briskin; T.Y. Odinets (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to determine purposefulness of early application of physical rehabilitation means for improvement of external respiration system functional state of women with post mastectomies syndrome. Material: in the research 135 women with post mastectomies syndrome, who endured radical mastectomy by Madden, participated. Women of main groups were trained in compliance with appropriate programs during one year. Effectiveness of trainings was controlled after half of year. Admission to trainings was given by oncologist. Patients of these groups belonged to third clinical group. At the beginning of dispensary period the groups were equal by all indicators of external system function. Results: it was found that early rehabilitation is more effective exclusively for indicators of bronchial patency. Complex, personality oriented program included: aqua-fitness; conditional swimming; health related aerobic and Pilates. It was found that after half year training advantages of early physical rehabilitation were noticed only in indicators of forced exhale volume at first second. Conclusions: we stated importance of early rehabilitation trainings of women with post mastectomies syndrome.